An assessment of funding gap in service provision at National Museums of Zimbabwe - Mugayi, Happymore K. (Midlands Sate University, 2015)
This study was carried out to assess the effects of the existence of the funding gap in service provision at National Museums and Monuments of Zimbabwe (NMMZ). The statement of the problem entails that measured service delivery at NMMZ has been greatly undermined due to the progressive reduction in government grant to support NMMZ operations. Factors such as high labour turnover, lack of maintenance of key museum equipment and infrastructure and the NMMZ current revenue collection system were nominated as persistent in the organisation and these factors are directly attributable to the existence of the funding gap. The research was carried out at NMMZ Head Office in Harare. The research found that high labour turnover and lack of maintenance of the museum equipment and infrastructure significantly affect service provision while the current NMMZ revenue collection system affects service delivery to a lesser extent. The findings of the research were presented in tables and graphs. It was recommended that NMMZ should use strategic business units (SBUs) as revenue generating units and set up sales promotion teams in order to alleviate the funding gap and normalise the organisation’s operations.